Atividade antinociceptiva do geraniol: estudos comportamentaise eletrofisiológicos - La Rocca, Viviana (2016)
The high incidence of pain in the general population has encouraged research about this theme. Products derived from plant species have been widely used in the pharmacological treatment of pain relief. Recent studies have reported the important role of monoterpenes, active compounds found in the essential oils of aromatic plants, having relevant analgesic and anti-inflammatory potential. The geraniol (GER) is a monoterpenic alcohol, found in >160 essential oil of plant species, especially Cymbopogon gender. In the literature consulted, several biochemical and pharmacological properties are shown of GER: antitumor, antimicrobial, antiinflammatory, antioxidant, gastric and intestinal protector, neuroprotective and antiarrhythmic. In this study was evaluated the antinociceptive activity of GER, not yet reported, by animal behavioral and electrophysiological in vitro models. Male and female adult Swiss mice were used. Initially the acute toxicity of GER was investigated by calculating the lethal dose 50 (LD50) by intraperitoneal (i.p.) (= 199.9 mg/kg) and oral (p.o.) (> 1 g/kg). In psychopharmacological screening, after the administration of single doses of GER (i.p. and p.o.), behavioral changes were observed indicating a depressant profile on the central nervous system (CNS) and/or peripheral nervous system (SNP), and relevant antinociceptive effect of geraniol. Therefore, more specific antinociceptive property evaluation tests were performed. The GER (12.5, 25 or 50 mg/kg i.p. and 50 or 200 mg/kg p.o.) decreased (p<0.001) the number of abdominal contractions induced by i.p. injection of acetic acid, when compared with the control. The opioid antagonist naloxone (5 mg/kg) administered subcutaneously (s.c.) in mice, subsequently treated with GER (25 mg/kg i.p.), did not reverse its antinociceptive activity. The GER (12.5, 25 and 50 mg/kg i.p.) reduced (p<0.001) paw licking time in the second phase (15-30 min, inflammatory phase) of the formalin test. Also, in the glutamate test was reduced (p<0.01) paw licking time when GER 50 mg/kg i.p. administered. In a subsequent step, it was investigated the effect of GER on the excitability of peripheral nerve fibers through extracellular recording in the sciatic nerve in mice. The GER presented depressant effect of the compound action potential (CAP), which was reversed after washing and recovery period. The GER blocked components of the CAP concentration-dependent manner and exposure time to the drug: 1 mM after 120 min for the first component (Aγ and Aβ fibers) and 0.6 mM after 90 min for the second (Aγ and Aδ fibers). The concentration, which induces 50% inhibition of the peak-to-peak amplitude of the PAC (IC50) for the GER was calculated, being equal to 0.48±0.04 mM. The conduction velocity was also reduced by exposure to GER from the 0.3 mM concentration, for the 1st component [46.18±2.60 m/s to 36.04±1.60 m/s; p<0.05 (n=7)] and the 2nd component [18.37±1.31 m/s to 12.71±0.56 m/s; p<0.001 (n=7)]. In conclusion, the results obtained show that GER has antinociceptive activity, mainly in pain related to inflammation. Participation of the opioid pathway in its mechanism of action is unlikely, but the modulation of glutamatergic neurotransmission in a dose-dependent manner is a possible mechanism. Its antinociceptive activity is also related to the reduction in peripheral neuronal excitability, firstly in thinner fibers Aδ, which are directly connected to the conduction pain.